Hubungan penggunaan media sosial, religiusitas dengan agresifitas mahasiswa fakultas ilmu kesehatan universitas muhammadiyah purwokerto - Setiowati, Anggun; Supriyadi, Supriyadi (Jurnal Keperawatan Muhammadiyah, 2020)
Background: Aggressivity was the behavior of individuals who intended to injure or harm other individuals who did not want this to happen. One of the causes of the emergence of aggressivity was the lack of basics of the faith. One of the factors that influenced aggressiveness was self-control which was obtained through the practice of religious values. Another factor that could affect aggressivity was social media. Social media has gradually brought us to a new cultural pattern and determined our mindset. Individual thought patterns would influence attitudes and behaviors including aggressivity. Objective: To figure out the correlation between the use of social media, religiosity and the aggressiveness of students of Health Science Faculty of Universitas Muhammadiyah Purwokerto. Method: The study was quantitative research by using correlation description design with cross sectional approach. The samples were taken by using simple random sampling technique. There were 71 people as the samples. Questionnaire of social media used Social Networking Usage Questionnaire: Development and Validation in an Indian Higher Education Context. Questionnaire of religiosity used The Centrality of Religiosity Scale (CRS), questionnaire of aggressivity used Aggression Questionnaire-Journal of Personality and Social Psychology questionnaire. The data were analyzed by using Chi Square test. Results: The results showed that based on Chi Square test, the relationship between the use of social media and aggressiveness obtained p = 0.0001. The relationship between religiosity and aggressivity obtained p = 0.0001. Conclusion: There is a correlation between the use of social media, religiosity and aggressivity of the students of Health Science Faculty, Universitas Muhammadiyah Purwokerto. Keywords: use of social media, religiosity, aggressivity